2016
DOI: 10.2147/ijn.s117745
|View full text |Cite
|
Sign up to set email alerts
|

New silver nanoparticles induce apoptosis-like process in <em>E. coli</em> and interfere with mammalian copper metabolism

Abstract: Silver nanoparticles (SNPs) are new functional materials that are widely used in biomedical and industrial technologies. Two main features that make SNPs valuable are their strong antibacterial effects and low toxicity to eukaryotes. In this study, SNPs were synthesized using a modified method of reducing the metal ions to their atomic state followed by crystallization. SNPs were characterized by UV/vis spectroscopy, X-ray diffractometry, atomic force microscopy, and transmission electron microscopy (TEM). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…Orlov et al reported that AgNPs acted positively against E. coli in a concentration-and time-dependent manner at a range of low concentrations. 25 Nonetheless, our results showed that the bactericidal effectiveness of AgNPs between drug-resistant and multidrug-resistant was of insignificance, indicating that the antibacterial mechanism of AgNPs may be different from that of antibiotics. By using TEM, Shrivastava et al observed the interactive process of AgNPs and E. coli: In the beginning, AgNPs anchored on the cell wall, where the potential negative charge groups existed, and then drilled holes in the wall and went into the cytoplasm, which finally resulted in the cell membrane perforation and cell lysis.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Orlov et al reported that AgNPs acted positively against E. coli in a concentration-and time-dependent manner at a range of low concentrations. 25 Nonetheless, our results showed that the bactericidal effectiveness of AgNPs between drug-resistant and multidrug-resistant was of insignificance, indicating that the antibacterial mechanism of AgNPs may be different from that of antibiotics. By using TEM, Shrivastava et al observed the interactive process of AgNPs and E. coli: In the beginning, AgNPs anchored on the cell wall, where the potential negative charge groups existed, and then drilled holes in the wall and went into the cytoplasm, which finally resulted in the cell membrane perforation and cell lysis.…”
Section: Discussionmentioning
confidence: 60%
“…15 Another group reported that no obvious destruction was viewed in the membrane of AgNPs-treated E. coli, although electron dense granules were found in the cytoplasm. 25 We found that after co-cultured with AgNPs, P. aeruginosa showed thinning cell wall and shrinking cell membrane, along with AgNPs, vacuoles, and agglutinative nucleoplasm inside the cell, while some bacteria became swollen or atrophic, which often accompanied fractured membrane and tremendous reduction of the cell contents. We conclude that AgNPs can be initially absorbed on the surface of the cell and then undermine the cell membrane, after that, the particles may be transported into the cytoplasm and imposed on a variety of macromolecules, either directly or indirectly, followed by DNA aggregation, protein degradation, or intracellular substance release and eventually, cell death.…”
Section: Discussionmentioning
confidence: 82%
“…It was proposed that silver ions dissociated from AgNPs bind with copper transporter proteins and cause copper sequestration, thus creating a condition that resembles copper starvation [199]. In mice treated with AgNPs, Cp oxidase activity in the blood serum was shown to decrease [200]. However, Cp expression and the relative contents of Cp protein in the Golgi complex and in the serum did not change [200].…”
Section: Interference Of Silver Nanoparticles (Agnps) In Copper Mementioning
confidence: 99%
“…In mice treated with AgNPs, Cp oxidase activity in the blood serum was shown to decrease [200]. However, Cp expression and the relative contents of Cp protein in the Golgi complex and in the serum did not change [200]. In addition, treatment with AgNPs did not influence liver SOD1 activity or serum alanine aminotransferase and aspartate aminotransferase content, i.e., AgNPs had no apparent toxic effects in mice.…”
Section: Interference Of Silver Nanoparticles (Agnps) In Copper Mementioning
confidence: 99%
“…[151][152][153][154] This first, step is dominated by the wall changes is followed by bacterial-cytosol leakage, lost the intracellular contents and finally the collapse of the cell or apoptotic-like bacterial cell death and formation of an amorphous mass of cell debris. 149,150,155 Due to the massive loss of the bacterial content the "ghost cells" morphology is used to describe lysed bacteria following this process. 150,156 Nanoparticles have the property to be adsorbed at the bacterial membrane mainly by electrostatic adhesion, a process mediated by surface charge of the particle-the zeta (ζ)-potentialand the outer layers of the bacterial cell wall.…”
Section: Antibacterial Effect and Mechanism Of Silver Nanoparticlesmentioning
confidence: 99%